The Magnetic Technology in Drinking Water of Laying Hens - Filoza Marwi; Osfar Sjofjan; Adharul Mutaqin; Muhammad Halim Natsir (Universitas Halu Oleo, 2021)
The experiment was conducted to know the best level of magnetic technology for improving water quality and to compare the use of magnetic technology (MT) and non-magnetic technology (NMT) in drinking water of the laying hens. This study had 2 experiment steps. The first step studied 3 levels (1350 Gs, 2700 Gs, 5400 Gs) of magnetic technology. The results showed that MT had a significant effect (p<0.05) on total dissolved solids (TDS), alkalinity, acidity, dissolved oxygen (DO), Escherichia coli, and no significant effect (p>0.05) on biochemical oxygen demand (BOD) and pH of drinking water. 2700 Gs used in the second step was the best result to improve water quality. Magnetic technology was used to treat drinking water of 288 ISA Brown birds aged 57-week assigned to 2 treatments (NMT and MT). MT showed no significant effect (p>0.05) on hen day production (HDP) but improved (p<0.05) the feed conversion ratio (FCR) of laying hens.Keywords: laying hens, magnet, production, water quality